2019
DOI: 10.1186/s12894-019-0452-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bilateral biopsy-detected prostate cancer on an active surveillance population

Abstract: Background To assess factors that can predict active surveillance (AS) failure on serial transrectal ultrasound guided biopsies in patients with low-risk prostate cancer. Methods We evaluated the records of 144 consecutive patients enrolled in AS between 2007 and 2014 at a single academic institution. Low risk inclusion criteria included PSA < 10 ng/ml, cT1c or cT2a, Grade Group (GG) 1, < 3 positive cores, and < 50% tumor in a single core with the majority having a PSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…11 In a retrospective study published in 2019, Wang et al observed that bilateral disease detected on Sbx was the strongest risk factor for AS failure. 12 On AS reclassification-free survival analysis, they found that bilateral disease was associated with earlier reclassification on followup biopsy (32 months for bilateral disease vs 119 months for unilateral disease). We expand on this work by adding that detection of bilateral disease using mpMRI of the prostate and Cbx, rather than Sbx alone, was significantly associated with disease progression in patients on AS and finding that PSAD at the time of AS enrollment additionally predicted future progression.…”
Section: Discussionmentioning
confidence: 99%
“…11 In a retrospective study published in 2019, Wang et al observed that bilateral disease detected on Sbx was the strongest risk factor for AS failure. 12 On AS reclassification-free survival analysis, they found that bilateral disease was associated with earlier reclassification on followup biopsy (32 months for bilateral disease vs 119 months for unilateral disease). We expand on this work by adding that detection of bilateral disease using mpMRI of the prostate and Cbx, rather than Sbx alone, was significantly associated with disease progression in patients on AS and finding that PSAD at the time of AS enrollment additionally predicted future progression.…”
Section: Discussionmentioning
confidence: 99%
“…Validation of the CCLO score to predict AS outcomes in our large, comprehensive cohort lends further credence to the utility of tabulating both tumor quantity and location on prostate biopsy. Prior research has shown that tumor location within the prostate has implications for progression on AS and genomic heterogeneity among multifocal tumors 9,10 . Despite this knowledge, the importance of recording intraprostatic tumor location on biopsy is not emphasized in current guidelines for localized prostate cancer risk stratification 1,11,12 .…”
Section: Discussionmentioning
confidence: 99%
“…The discriminative ability to predict GR using Harrell's c-index implications for progression on AS and genomic heterogeneity among multifocal tumors. 9,10 Despite this knowledge, the importance of recording intraprostatic tumor location on biopsy is not emphasized in current guidelines for localized prostate cancer risk stratification. 1,11,12 The CCLO score can help to fill this gap by providing a shorthand notation of the number of prostate sextants involved with cancer in addition to the total volume of biopsied disease.…”
Section: Mcclo Score Development and Assessmentmentioning
confidence: 99%
“…2 Another study found that bilateral Gleason 6 involvement predicted for early progression of disease and should be cautionary for AS. 3 In our practice, where Black individuals comprise three-quarters of the patient population, we recently showed that aggressive prostate cancer diagnoses are increasing. 4 Therefore, we caution vigilance for AS especially for high-risk groups such as Black men and those with adverse tumor-specific features.…”
mentioning
confidence: 99%